The Different Effect of Active Learning on Student Learning Outcomes in Intervention and Control Schools (International Journal of Active Learning, 2022)
The purpose of this research is to know the effect of the differences in the implementation of active learning to mathematics and science scores in interventional schools and control schools as well as the cohort effectiveness interventions to improve student learning outcomes. This is a quantitative research experiment conducted in 7 provinces in Indonesia consisting of 50 districts and cities. Total samples of 1,075 schools consisting of 569 partner schools are intervened and 506 control schools. Test the average difference using Mann Whitney. To determine the cohort effective intervention used MANOVA. The results showed that mathematical and science scores were better in interventions school compared to the results in control schools. Bonferroni test the mathematical score suggests that the best intervention is the third cohort. The Bonferroni test of the science score shows the second cohort intervention and the third cohort is equally good.